Learning Basketball - Barth, K.; Bösing, L. (Meyer & Meyer Sport (UK) Ltd., 2009)
Basketball is the fastest team sport and has lots of action. Skillful handling of the ball and good team play with your friends make for lots of fun and many points. In addition to playing with your friends you work hard on basic techniques like passing, catching, dribbling, smart ways to get open, and of course making baskets.